Reconstructing Islamic Strategic Management A Comparative Analysis of Michael Porter's Competitive Advantage Theory and The Principle of Al-Falah - Putri Rahayu; Yogi Fajar Permata; Indah Puji Safitri; Diah Lestari; Agustina Mutia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to reconstruct an Islamic strategic management framework through a comparative analysis between Michael Porter’s Competitive Advantage theory and the principle of Al-Falah. The research is motivated by the dominance of conventional strategic management paradigms that prioritize competitiveness and economic performance while often underemphasizing ethical, social, and spiritual dimensions of organizational success. A qualitative methodology was employed using library research and conceptual comparative analysis of relevant scholarly literature. Data were collected from academic books and peer-reviewed journal articles, then analyzed using content and comparative analysis techniques. The findings show that both Competitive Advantage and Al-Falah share the objective of achieving organizational sustainability, yet they differ fundamentally in philosophical foundations, strategic objectives, performance indicators, and stakeholder orientation. Competitive Advantage emphasizes market positioning, profitability, and efficiency, whereas Al-Falah integrates material success with ethical values, social justice, collective welfare, and accountability to God. The study highlights that conventional strategic management tends to focus on economic outcomes, while the Islamic perspective expands success into moral and spiritual dimensions. Based on these differences, the study proposes a reconstructed Islamic Strategic Management model that integrates competitiveness with principles of tawhid, amanah, maslahah, and stakeholder welfare. This integrated framework is expected to provide a more holistic understanding of organizational success that balances economic performance with ethical responsibility and spiritual accountability in contemporary organizational contexts for sustainable development and long-term institutional resilience in modern organizations.